1998
DOI: 10.1093/emboj/17.14.3886
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of mitochondrial targeting signals with acidic receptor domains along the protein import pathway: evidence for the 'acid chain' hypothesis

Abstract: Mitochondrial precursor proteins with basic targeting signals may be transported across the outer membrane by sequential binding to acidic receptor sites of increasing affinity. To test this 'acid chain' hypothesis, we assayed the interaction of mitochondrial precursors with three acidic receptor domains: the cytosolic domain of Tom20 and the intermembrane space domain of Tom22 and Tim23. The apparent affinity and salt resistance of precursor binding increased in the order Tom20ϽTom22 (internal)ϽTim23. Precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 36 publications
3
117
0
4
Order By: Relevance
“…It is evident, however, that Tim23 represents the presequence-sensitive channel of the mitochondrial inner membrane. Only Tim23 contains a large N-terminal domain exposed to the intermembrane space that binds presequences with high affinity 13,17,19,21,22 ; Tim17 lacks such a domain. Both functions of Tim23, as presequence receptor and channel, are intimately linked, because the high-affinity influence of a presequence on the channel formed by the C-terminal domain is mediated by the N-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident, however, that Tim23 represents the presequence-sensitive channel of the mitochondrial inner membrane. Only Tim23 contains a large N-terminal domain exposed to the intermembrane space that binds presequences with high affinity 13,17,19,21,22 ; Tim17 lacks such a domain. Both functions of Tim23, as presequence receptor and channel, are intimately linked, because the high-affinity influence of a presequence on the channel formed by the C-terminal domain is mediated by the N-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, this model does not fit the observation that yeast mitochondria containing overexpressed Tim23 import significantly more matrix-targeted preprotein than do control mitochondria 21 . Different functions have been reported for Tim23, including roles as a voltage-sensitive presequence receptor 11,21,22 and as a regulator, but not as a structural element of the multiple conductance channel of the inner membrane 11 . The observation that purified Tim23 alone forms a presequence-sensitive channel suggested that it would be revealing to compare the channel characteristics of purified Tim23 with that of the multiple conductance channel of the inner membrane of yeast mitochondria.…”
Section: Characteristics Of the Presequence Translocasementioning
confidence: 99%
See 1 more Smart Citation
“…For matrixtargeted preproteins, it was proposed that the TOM complex provides binding sites on each side of the outer membrane. The cytosolic domains of Tom20, Tom22, and Tom5 form the cissite of the TOM complex, which binds presequences reversible in a salt-labile manner (29,(59)(60)(61). Tom40 seems to be largely responsible for the formation of the trans-site, which is localized on the inner face of the membrane (62).…”
Section: Translocation Across the Outer Membranementioning
confidence: 99%
“…Therefore, it seems possible if not likely that the translocation across the outer membrane is driven by the sequential interaction of presequences with different modules of the TOM complex that bind the preproteins with increasing af nity (31,59,60). A model was put forward in which negative charges of the transport components would play a decisive role in the stepwise forward movement of the presequences ("acid-chain-hypothesis") (65).…”
Section: Translocation Across the Outer Membranementioning
confidence: 99%